INFORMAL AND FORMAL SECTORS PARTNERSHIP IN URBAN WASTE MANAGEMENT (Case Study: Non-Organic Waste Management in Semarang) - Djoko Indrosaptono; Imam Buchori; Joesron Alie Syahbana (International Journal of Science and Engineering)
The urban waste management is still crucial issues in most regions in Indonesia. Urban waste is considered as a cultural issue because of its impact on various life factors , especially in big cities such as Jakarta, Semarang, Surabaya, Bandung, Palembang and Medan. Currently, the average productivity of the urban waste is 0.5 kg / capita / day. If this is multiplied by number of people in some cities in Java and Bali, the total waste will reach about 100,000 tons / day. This number will still increase by increasing population growth. Therefore, the urban waste management is very important for cities in Indonesia, alhough currently not many cities applied the urban waste management system. Urban waste management in Indonesia is not merely caused by formal sector, but it is also supported by informal sector in reducing daily production waste up to 30%. The informal sector management is mainly conducted by sorting the waste to recycleable or not. The recycleable waste is then sold back to the mills to be converted to other valuable products. This reserach was aimed to evaluate the partnership between formal and informal sector in reduction of waste production in Semarang city through urban waste management system. The research about informal sector was conducted by communal interaction and qualitative analysis focusing at Semarang City especially at Old Town area. The research has provided substantive knowledge of informal sector partnerships and formal sector in urban waste management with case inorganic waste management in the city of Semarang through 3R (recycle, reuse and reduce) knwoledge management. Basic knowledge of the structure / surface is characterized by empirical knowledge which was easily caught by the direct perspective of human. Middle knowledge could be adjusted to different loci